Comprensión lectora y pensamiento crítico en estudiantes de quinto de secundaria de una institución educativa militar - La Perla - Callao - Barranzuela Yenque, José Isaías (2012)
his investigation shows a correlational analysis among the reading comprehension and the critical thinking of students in fifth grade of secondary school from a military educational institution from La Perla (Callao), 153 students with ages among 14 and 18 years joined in this study. The sample that was utilized no is probabilistic of available type , as to it was taken as an analysis unit for the fifth grade students of secondary school. The investigation is descriptive correlational. The instruments used were: the Silva & Tapia’s Test of Reading Comprehension (1982) and the Milla’s Test of Critical Thinking Evaluation (2012). The obtained results: Low reading comprehension levels and high critical thinking levels. A little significant relation among both variables exists. Finding also significant relations among the reading comprehension and the critical thinking's dimensions that vary among 0,045 to 0,225. There were no significant differences for sections.